Pengaruh Tarif Pajak, Pengetahuan Perpajakan dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Pelaku UMKM: Studi Kasus pada Kecamatan Sedati, Sidoarjo - Narita Septia Ayu Sugiharsono; Hero Priono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of tax rates, tax knowledge, and tax sanctions on taxpayer compliance. This research employs a quantitative approach using primary data. The population of this study consists of Micro, Small, and Medium Enterprise (MSME) taxpayers in Sedati District, Sidoarjo. The sampling technique used is simple random sampling. Data were collected through questionnaires, with a total of 50 respondents. The data analysis technique applied is multiple linear regression using SPSS version 22.0. The results indicate that tax rates do not have a significant effect on taxpayer compliance, and tax knowledge also does not have a significant effect on taxpayer compliance among MSME taxpayers in Sedati District, Sidoarjo. However, tax sanctions have a significant effect on taxpayer compliance among MSME taxpayers in Sedati District, Sidoarjo.